1978
DOI: 10.1007/bf01944708
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the etiology of the experimental neuropathy from industrial adhesive (glues)

Abstract: Chickens treated by paintbrushing with glue distillate (used in shoe industries), hydrocarbon mixture and TOCP in hexane, developed paralysis (4/5); in these, we have demonstrated a diffuse degeneration of the myelinic sheath of the peripheral and central neurites. Besides TOCP, cyclohexane (because of its higher concentration in the glue distillate and in the hydrocarbon mixture) may be indicated as responsible for occupational neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Potassium dichromate is a formula of chromium and it has stayed used in the induction of hepaticinjury [10][11][12][13] . And it is described that acute contact encourageshepatic structural alterationin the hepatocytes and phospholipid oxidation in the liver 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Potassium dichromate is a formula of chromium and it has stayed used in the induction of hepaticinjury [10][11][12][13] . And it is described that acute contact encourageshepatic structural alterationin the hepatocytes and phospholipid oxidation in the liver 13 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that peripheral neuropathy rate in abusers who inhale volatile substances varies between 7% and 62% depending on the substance content (Rosen 1984). Peripheral nerve toxicity of toluene could not be fully identified and has been reported to be at low rates (Franchini et al . 1978; Lolin 1989).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in some studies, peripheral neuropathy with motor dominance have been observed following toluene use in animal experiments and humans (Goto et al . 1974; Franchini et al . 1978; Streicher et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation